2009
DOI: 10.1111/j.1471-4159.2009.06023.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of catecholamine release and tyrosine hydroxylase in human adrenal chromaffin cells by interleukin‐1β: role of neuropeptide Y and nitric oxide

Abstract: J. Neurochem. (2009) 109, 911–922. Abstract Adrenal chromaffin cells synthesize and secrete catecholamines and neuropeptides that may regulate hormonal and paracrine signaling in stress and also during inflammation. The aim of our work was to study the role of the cytokine interleukin‐1β (IL‐1β) on catecholamine release and synthesis from primary cell cultures of human adrenal chromaffin cells. The effect of IL‐1β on neuropeptide Y (NPY) release and the intracellular pathways involved in catecholamine release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 74 publications
(192 reference statements)
2
33
0
Order By: Relevance
“…In turn, neuropeptides are known to regulate the synthesis and release of cosecreted catecholamines. For example, it has been reported that vasoactive intestinal peptide, secretin, and neuropeptide Y increase catecholamine synthesis by activation of tyrosine hydroxylase in human adrenal chromaffin cells (Ip et al, 1984;Cavadas et al, 2001;Rosmaninho-Salgado et al, 2009). The regulatory circuit is completed when this neuropeptide-triggered increase in catecholamines eventually leads to a reduction in neuropeptide production, accomplished by catecholaminergic inhibition of neuropeptide processing enzymes, as demonstrated in the present study.…”
supporting
confidence: 73%
“…In turn, neuropeptides are known to regulate the synthesis and release of cosecreted catecholamines. For example, it has been reported that vasoactive intestinal peptide, secretin, and neuropeptide Y increase catecholamine synthesis by activation of tyrosine hydroxylase in human adrenal chromaffin cells (Ip et al, 1984;Cavadas et al, 2001;Rosmaninho-Salgado et al, 2009). The regulatory circuit is completed when this neuropeptide-triggered increase in catecholamines eventually leads to a reduction in neuropeptide production, accomplished by catecholaminergic inhibition of neuropeptide processing enzymes, as demonstrated in the present study.…”
supporting
confidence: 73%
“…The inclusion of the NPY Y1 receptor antagonist (BIBP 3226) or immunoneutralization of NPY suppressed the IL-1b stimulated catecholamine release. This investigation has recently been extended to demonstrate a similar IL-1b-induced catecholamine secretion from isolated human adrenal medullary chromaffin cells (Rosmaninho-Salgado et al 2009). As with the mouse studies, IL-1b also increased NPY secretion and blockade of the NPY receptor (or the inclusion of anti-NPY antibodies) suppressed the elevation in catecholamine secretion.…”
Section: Interleukin-1mentioning
confidence: 85%
“…The IL-1b-stimulated catecholamine secretion was accompanied by an increase in ser-40 phosphorylation of tyrosine hydroxylase and a delayed rise in the enzyme's expression-responses indicative of increased catecholamine synthesis. The inclusion of selected pharmacological inhibitors revealed a complex signalling pathway but led Rosmaninho-Salgado et al (2009) to suggest that IL-1b stimulation of catecholamine release from chromaffin cells involves three different pathways namely, ERK1/2, NO-PKC and NO-guanylyl cyclase (Rosmaninho-Salgado et al 2009). While further experiments will be required to tease apart these complexities, these data indicate that IL-1b and NPY are involved in a regulatory loop between immune and adrenal medullary cells which is likely to be of relevance during inflammatory conditions.…”
Section: Interleukin-1mentioning
confidence: 99%
“…In human chromaffin cells, NPY has been shown to positively regulate catecholamine secretion (Rosmaninho-Salgado et al 2009). Among the six genes, Y1, Y2, Y3, Y4, Y5, and Y6 that have been described as coding for NPY receptors, Y6 is a pseudogene in human that codes for a truncated nonfunctional protein.…”
Section: Introductionmentioning
confidence: 99%